The essential guides to business for artists and designers - Branagan, Alison (Bloomsbury, 2017)
"This new edition of the best-selling business handbook for artists and designers is a comprehensive guide to setting up a profitable, professional art or design practice. Written by an expert who teaches entrepreneurship and business start-up, this book leads the reader through the most important aspects of running a creative business, from how to make a living to innovation and managing business growth. Topics include: * Working with new technologies and social media * Pricing work and financial planning * Managing legal and copyright issues * Building networks and successful negotiation tactics * Planning for growth and exploiting future trends New to this expanded edition are: * International profiles of creatives who run thriving businesses * Templates, forms and spreadsheets to copy or download from the companion website * Exercises to build business skills * An extended list of useful resources * A chapter on how to grow your business * An overview of the current business environment for entrepreneurs, including opportunities such as trading with a smart phone, copyright protection using QR codes, selling internationally, crowd sourcing for funding, and setting up a pop-up shop * Updated tax and legal information on setting up a business based in the UK or US * Expanded information on trading internationally The book is printed in a dyslexic-friendly font and includes illustrated mind maps and colour pictures throughout"--Resumé vydavatele